Olfactory Receptors Modulate Physiological Processes in Human Airway Smooth Muscle Cells - Kalbe, Benjamin; Knobloch, Jürgen; Schulz, Viola M.; Wecker, Christine; Schlimm, Marian; Scholz, Paul; Jansen, Fabian; Stoelben, Erich; Philippou, Stathis; Hecker, Erich; Lübbert, Hermann; Koch, Andrea; et al. (Frontiers in Physiology, 2016)
Pathophysiological mechanisms in human airway smooth muscle cells (HASMCs) significantly contribute to the progression of chronic inflammatory airway diseases with limited therapeutic options, such as severe asthma and COPD. These abnormalities include the contractility and hyperproduction of inflammatory proteins. To develop therapeutic strategies, key pathological mechanisms and putative clinical targets need to be identified. In the present study, we demonstrated that the human olfactory receptors (ORs) OR1D2 and OR2AG1 are expressed at the RNA and protein levels in HASMCs. Using fluorometric calcium imaging, specific agonists for OR2AG1 and OR1D2 were identified to trigger transient Ca2+ increases in HASMCs via a cAMP-dependent signal transduction cascade. Furthermore, the activation of OR2AG1 via amyl butyrate inhibited the histamine-induced contraction of HASMCs, whereas the stimulation of OR1D2 with bourgeonal led to an increase in cell contractility. In addition, OR1D2 activation induced the secretion of IL-8 and GM-CSF. Both effects were inhibited by the specific OR1D2 antagonist undecanal. We herein provide the first evidence to show that ORs are functionally expressed in HASMCs and regulate pathophysiological processes. Therefore, ORs might be new therapeutic targets for these diseases, and blocking ORs could be an auspicious strategy for the treatment of early-stage chronic inflammatory lung diseases.